STRATEGI PEMBELAJARAN IPA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN SIKAP ILMIAH SISWA DI SDN 111/I MUARO BULIAN - Khoirunnisa; Salsabilla Rahma Junita; Asti Amalia Sari; Rahmad Halomoan (STKIP Subang, 2025)
This paper discusses the importance of implementing innovative learning strategies in Natural Science (IPA) in elementary schools, specifically at SDN 111/I Muaro Bulian. The primary focus is on how science learning can develop students' skills and knowledge. The method used is a literature review of various journals, books, and prior observation. The analysis shows that inquiry-based learning, discovery learning, and project-based learning models can improve students' critical thinking skills, problem-solving skills, and scientific attitudes.